DRIVERS AND CONSTRAINTS FOR BUSINESS PROCESS OUTSOURCING IN SOUTH AFRICAN CORPORATE AND INVESTMENT BANKING OPERATIONS - van der Westhuizen, Sarel Jacobus (My University, 2013)
The research sought to identify and analyse the business drivers and constraints that lead South African corporate and investment banks to either outsource operations processing to external service providers, or to conduct such operations processing internally. The research took the form of a simple, interpretive study and followed a qualitative research approach, using in-depth, semi-structured interviews with executive management representatives in the wholesale banking operations industry in South Africa, including banks, outsourcing service providers and industry bodies. The findings from the research identified the drivers for outsourcing as cost reduction, revenue growth, increased operating efficiency, organisational effectiveness and human resource development, improved strategic control, process control and operational risk management, external environmental factors and enhanced competitiveness. The constraints identified through the research were diminished strategic control, lessened ability to contend with competitive threats, cost escalations, insufficient management capability, human resources interests, diminished process control, increased operational risk, reduced organisational effectiveness, operating efficiency and external environment factors. The drivers for outsourcing stem from the superior capability maturity levels of outsourcing service providers, the opportunity to free-up incumbent senior management and leadership to focus on core responsibility areas, the certainty and control inherent in formal partnerships, as well as the opportunity to leverage the capital resources of outsourcing vendors. Conversely, the constraints for outsourcing stem from inability to implement processing changes, operating model complexity, misaligned management cultures, lingering concerns about reputational risk, as well as lagging capability maturity levels in specialist processing areas.
MBA thesis
Keywords: Business process outsourcing; Outsourcing